Pelagic Fish Caught Around Rumpon Ijuk Using Fishing Gear in Aceh Singkil Regency - Khusnul Khatimah; Said Radius; Firma Warni; Hafinuddin Hafinuddin; Muhammad Rizal; Samsul Bahri; Afdhal Fuadi; Ihsanul Khairi (Journal of Aceh Aquatic Sciences, 2023)
AbstractRumpon is one of the environmentally friendly fishing gear that functions to collect fish and can be used as a fishing ground. This research was carried out in the waters of Aceh Singkil in December 2022 and January 2023. The identification results were 6 species from 4 families of pelagic fish caught around rumpon in Aceh Singkil Waters, namely Elagatis bipinulata, Carangoides ignobilis, Scombrioides tala, Euthynus affinis, Selar crumenophthalmus, and Sardinella lemuru. The diversity index of Balai Island is low with a value of 0.90 and around Baguk Island the diversity index is high with a value of 0.93. The uniformity of pelagic fish around Balai Island is relatively low with a value of 0.30 and around Baguk Island the uniformity index is high with a value of 0.85. While the Pelagic fish dominance index around Balai Island is relatively high with a value of 0.68 and around Baguk Island the dominance index is also low with a value of 0.43.Keywords: Aceh Singkil, ikan pelagis, rumpon